Proceedings of the 2017 5th International Conference on Mechatronics, Materials, Chemistry and Computer Engineering (ICMMCCE 20 2017
DOI: 10.2991/icmmcce-17.2017.231
|View full text |Cite
|
Sign up to set email alerts
|

Co-simulation Research on Flow Pulsation Characteristics of Plunger Pump Based on AMESim and ADAMS

Abstract: Abstract:Flow pulsation characteristic is the inherent characteristic of the axial plunger pump, and it is an important factor that affects the working performance and the stability of the hydraulic system. To reduce the flow pulsation of axial plunger pump, theoretical analysis of the motion characteristics and flow pulsation characteristic; The co-simulation model of axial plunger pump was established using ADAMS and AMESim, The influence of different structural parameters on the pulsation of axial plunger p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…2 To reduce the flow and pressure pulsations, which can damage the motor and its devices in the system, many researchers have optimised the structure of the plunger pump and designed control algorithms of the pump control system. [3][4][5] Qian [6][7] established a simulation model of the plunger pump using AMESim and ADAMS software. They studied the flow-pulsation dependence on the number of pistons, rotating speed and swash plate inclination angle of the axial plunger pump, and summarized the law of flow-pulsation change.…”
Section: Introductionmentioning
confidence: 99%
“…2 To reduce the flow and pressure pulsations, which can damage the motor and its devices in the system, many researchers have optimised the structure of the plunger pump and designed control algorithms of the pump control system. [3][4][5] Qian [6][7] established a simulation model of the plunger pump using AMESim and ADAMS software. They studied the flow-pulsation dependence on the number of pistons, rotating speed and swash plate inclination angle of the axial plunger pump, and summarized the law of flow-pulsation change.…”
Section: Introductionmentioning
confidence: 99%
“…Wang Yu et al [23] established a plunger pump model through AMESim, simulated the outlet flow characteristics of the hydraulic oil under the rated load pressure of the plunger pump, obtained the fluid pressure pulsation function expression, and the influence of fluid pressure pulsation at the outlet of the aircraft engine pump on pipeline structure vibration was analyzed. Qian Wenxin et al [24] established a simulation model based on the AMESim, and obtained flow pulsation curves under different plunger numbers, rotation speeds, and swash plate inclination angles. The research results showed that the flow pulsation of the axial piston pump decreases with the increase of the number of plungers, the increase of the speed, and the increase of the inclination of the swash plate.…”
Section: Introductionmentioning
confidence: 99%